Changing Forms of Corruption in India*. (12th January 2018) - GUPTA, AKHIL
Abstract: This article has four important goals. First, I want to ask why liberalization and market-friendly reforms failed to curb corruption in India. Indeed, confounding the predictions of most proponents of reform, corruption seems to have increased after the neoliberal reforms of 1991. Second, I aim to develop a typology in which the importance of particular sectors to corrupt practices is highlighted and explained. Third, I point out that India has failed to make the 'transition' historically seen in low-income countries as they develop. Nation-states have in the past moved from a system of vertical corruption—marked by the extraction of small sums from a large number of transactions with citizens in everyday life—to a system of horizontal corruption, in which governmental elites extract large sums in a small number of transactions from corporate and commercial bodies. Finally, I argue that anti-corruption movements cannot be understood without paying attention to the affective and emotional ties that bind citizens to the state. We have to take account of contradictory feelings about the state: cynicism about the state and popular anger against corruption on one side, and an attachment to popular sovereignty and patronage on the other. These contradictory sentiments will better enable us to understand the conjunctures that lead to effective institutional change.